2017
DOI: 10.1097/phm.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

Memory Rehabilitation Strategies in Nonsurgical Temporal Lobe Epilepsy

Abstract: People with temporal lobe epilepsy (TLE) who have not undergone epilepsy surgery often complain of memory deficits. Cognitive rehabilitation is employed as a remedial intervention in clinical settings, but research is limited and findings concerning efficacy and the criteria for choosing different approaches have been inconsistent. We aimed to appraise existing evidence on memory rehabilitation in nonsurgical individuals with temporal lobe epilepsy and to ascertain the effectiveness of specific strategies. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Although there has been increasing emphasis on screening and early identification of comorbidities, there is a clear need for systematic intervention trials to improve practice and patient outcomes. Appearing are reports of interventions designed to improve memory and cognition (Adams et al, 2017; Caller et al, 2016; Del Felice et al, 2017; Farina, Raglio, & Giovagnoli, 2015; Jackson, Makin, & Baker, 2015), mood disorders (Gandy, Sharpe, & Perry, 2013), and epilepsy self-management (Jobst & MEW network, 2017; Shegog et al, 2013; Wagner et al, 2017). Both pharmacologic and behavioral interventions will be critical to improving patient life outcomes in patients with chronic epilepsy (Del Felice et al, 2017) and those who have undergone epilepsy surgery (Mazur-Mosiewicz et al, 2015).…”
Section: Where Will (Should) Neuropsychology Head During the Next Decmentioning
confidence: 99%
“…Although there has been increasing emphasis on screening and early identification of comorbidities, there is a clear need for systematic intervention trials to improve practice and patient outcomes. Appearing are reports of interventions designed to improve memory and cognition (Adams et al, 2017; Caller et al, 2016; Del Felice et al, 2017; Farina, Raglio, & Giovagnoli, 2015; Jackson, Makin, & Baker, 2015), mood disorders (Gandy, Sharpe, & Perry, 2013), and epilepsy self-management (Jobst & MEW network, 2017; Shegog et al, 2013; Wagner et al, 2017). Both pharmacologic and behavioral interventions will be critical to improving patient life outcomes in patients with chronic epilepsy (Del Felice et al, 2017) and those who have undergone epilepsy surgery (Mazur-Mosiewicz et al, 2015).…”
Section: Where Will (Should) Neuropsychology Head During the Next Decmentioning
confidence: 99%
“…This protocol describes a planned randomized waitlist-control trial of CoRE in epilepsy. The study was designed to address major research gaps identified through recent systematic literature reviews in this field, as discussed below ( 5 , 6 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even wakeful resting after having learnt new data has been demonstrated to improve long-term recollection [107,108]. Del Felice et al reviewed existing memory rehabilitation studies in patients with TLE and proposed that cognitive strategies, external mental aids, computerized training and non-invasive brain stimulation should be further explored to provide behavioral and mental techniques for reducing the burden of forgetfulness [109].…”
Section: Memory Rehabilitationmentioning
confidence: 99%